Makna Dan Fungsi Pantang Larang Masyarakat Melayu Peranap di Kecamatan Peranap Kabupaten Indragiri Hulu - Adel Via; Erni, Erni (UIR PRESS, 2021)
This research Pantang-larang is a belief by the ancient Malay community that is related to the customs/traditions and cultural heritage of their ancestors. Most of that taboo is passed down from generation to generation orally. Taboos are used by parents in order to educate the community to become a moral generation, especially the younger generation in order to lead to the application of good values ​​that can be practiced in life. However, now taboos are slowly disappearing in this modern age, because the current generation only sees taboos as a threat, frightening and smells of myth and death. This study examines the type, meaning and function of the taboo of the Malay community Peranap in Peranap District, Indragiri Hulu Regency with the problem of this research, (1) What are the types of taboo Malay community Peranap Peranap District Peranap Indragiri Hulu Regency ?, (2) What is the meaning contained in the taboo of the Malay community Peranap Peranap District Peranap Indragiri Hulu Regency ?, (3) What is the function contained in the taboo of the Malay community Peranap Peranap District Peranap Indragiri Hulu Regency ?. The purpose of this research is to explain and describe the problems associated with the formulation of the problem is to determine the type, meaning and function of taboos. For the analysis the authors used the taboo theory by Effendy (2003) meaning by Pateda (2010) and function by Danandjaya (1991). The method used by researchers in this study is a descriptive method, with a qualitative approach. While the technique that researchers use in this research is the technique of interviewing the informant directly, then record all about the taboos found from the informant and this study also uses observation techniques, researchers who are also Malay community Peranap also heard people around researchers who use taboo and from that experience, the researcher finally took the data from what the researcher had heard in addition to the researcher's data that is taboo.